Shedding light on the currencies, prices, wages, and living level in Damascus in the first half of the nineteenth century. (Damascus University Journal of arts and humanities sciences, 2021)
The research highlighted the types of currencies and their value that were circulating during the first half of the nineteenth century. The research also  showed the efforts of the Shura Council to control prices and control the balance and punish the cheaters (Falaqa(Various tables were presented for the prices of vegetables, fruits, wheat, barley, meat, building materials and used materials. The research also showed the real estate prices and wages, and highlighted the important aspects of salaries and wages of senior officials and the Aguat Damascus with its eight divisions and salaries of scientists and others, where we show through these salaries the standard of living in Damascus for most segments of the population.
Keywords: Shedding light on the currencies, prices, wages, and living level in Damascus in the first half of the nineteenth century.